Revision and cladistic analysis of the Neotropical Genus Thecomyia Perty (Diptera: Sciomyzidae) - Marinoni, Luciane; Steyskal, George C.; Knutson, Lloyd (Zootaxa, 2003)
A revision of the genus Thecomyia Perty, 1833 and a cladistic analysis are presented. Four species names were previously available: T. longicornis Perty, 1833; T. lateralis (Walker, 1858); T. limbata (Wiedemann, 1819) and T. trilineata Hendel, 1932. Herein we designate a lectotype for T. longicornis, T. trilineata is considered a synonym of T. lateralis and nine additional new species are described: T. abercrombiei, T. autazensis, T. bonattoi, T. chrysacra, T. mathisi, T. naponica, T. papaveroi, T. signorelli and T. tricuneata. The cladistic analysis was done using Hennig86 and is based on 21 morphological characters. The analysis was performed using "implicit enumeration" along with "branch and swapping" and resulted in one tree. Two main clades were formed. The first one: (T. tricuneata (T. longicornis (T. chrysacra + T. signorelli))) and the second: (T. autazensis (T. papaveroi + T. naponica)) + (T. limbata (T. abercrombiei (T. lateralis (T. bonattoi + T. mathisi)))).